A novel technological performance measurement indicator: a smart manufacturing approach - Luisa Maria Tumbajoy Cardona; Mariela Muñoz-Añasco (Gestão & Produção, 2023)
Abstract The implementation of digital manufacturing technologies (DMTs) represents the beginning of transforming a manufacturing system towards a smart manufacturing system (SMS). Assessing the performance of the DMTs implemented is essential to meet the objectives in a SMS and allows identifying their usefulness. However, estimating this performance is a challenging task due to the heterogeneous characteristics of the DMTs, such as the origin of information, capacity, connectivity, etc. Although some SMS performance measurement metrics are known, none are intended to identify the performance of DMTs. This article follows a methodology for the construction of technological performance indicators and proposes a novel indicator based on the individual characteristics of the DMTs and the smart factory concept of interoperability. The proposed indicator allows approaching the behavior of one or multiple DMTs implemented simultaneously and introduces a quantifiable measurement that can be applied to any industrial process. It is noteworthy, that such an indicator is not present in the literature and may be of great interest to enterprises currently implementing DMTs related to SMS. The applicability of the indicator considering multiple DMTs is validated through an illustrative test case.